Thymic Epidermoid Cyst: Clinical and Imaging Manifestations of This Rare Anterior Mediastinal Mass - Jawad M. Qureshi; Brian Pagano; Jeffrey Mueller; Lana Schumacher; Claudia Velosa; Matthew S. Hartman (Case Reports in Radiology)
Thymic epidermoid cysts are an extremely rare entity. These arise from epidermal cells that migrate to the thymus. The radiologic diagnosis of this rare lesion is challenging. We describe a case of an otherwise healthy 35-year-old woman who presented with an acute onset of chest pain and shortness of breath. She was found to have an anterior mediastinal mass. The imaging findings were, however, not characteristic for any single diagnostic entity. Since the imaging was inconclusive, surgical resection was performed for definitive diagnosis. The mass was found to be a thymic epidermoid cyst. This case underlines the significance for radiologists to be aware that epidermoid cysts can occur in the thymus and should be considered in the differential diagnosis for a heterogeneous anterior mediastinal mass.